Extreme events : robust portfolio construction in the presence of fat tails - Kemp, Malcolm H. D. (Wiley, 2011)
"With slight exaggeration, a case can be made that modern finance has been built, in practice, if not in theory, on implicit tolerance and widespread ignorance of extreme events. Jean Pierre Landau, Deputy Governor, Banque du France Markets are fat-tailed; extreme outcomes occur more often than many might hope, or indeed the statistics or normal distributions might indicate. In this book, the author provides readers with the latest tools and techniques on how best to adapt portfolio construction techniques to cope with extreme events. Beginning with an overview of portfolio construction and market drivers, the book will analyze fat tails, what they are, their behavior, how they can differ and what their underlying causes are. The book will then move on to look at portfolio construction techniques which take into account fat tailed behavior, and how to stress test your portfolio against extreme events. Finally, the book will analyze really extreme events in the context of portfolio choice and problems. The book will offer readers: Ways of understanding and analyzing sources of extreme events Tools for analyzing the key drivers of risk and return, their potential magnitude and how they might interact Methodologies for achieving efficient portfolio construction and risk budgeting Approaches for catering for the time-varying nature of the world in which we live Back-stop approaches for coping with really extreme events Illustrations and real life examples of extreme events across asset classes This will be an indispensible guide for portfolio and risk managers who will need to better protect their portfolios against extreme events which, within the financial markets, occur more frequently than we might expect."--